Kosovo problem and options to final status - Troşala, Arzu. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
Few places in the world of the size and population of Kosovo have received an attention both among policy makers and academics. Why is Kosovo important? The Kosovo problem deserves attention because it occupies a central position in the Balkans both geographically and strategically and its development, whether positive or negative, will have effects throughout the region. Among all the future status of Kosovo has yet to be defined and the security problem and the future of peace keeping operation need to be resolved. The guns have fallen silent in Kosovo but a lasting peace has yet to come. Difficulties over the solution between parties (Albanians and Serbs) and unsolved status of Kosovo possess obstacles in creating peace, stability and prosperity in the region as well as its integration in Europe. The purpose of this study is to determine the causes and course of Kosovo problem and analyze possible alternative solutions to the Kosovo problem.
Keywords: Albanians -- Yugoslavia -- Kosovo (Serbia)